The Influence of Effective Communication on the Understanding of the Independent Curriculum in Grade X Students of Pasundan 1 Vocational School, Bandung - Yulia Segarwati; Zahrah Nabila Azka; Rafi Rizalul Haq; Salsabila Rizqan Daru (LP2M IAIN Palopo, 2025)
Effective communication is one of the important factors in the learning process, including in the implementation of the Merdeka Curriculum which is currently being implemented in various educational institutions in Indonesia. With good communication between teachers and students, the understanding conveyed regarding the material and concepts of the Merdeka Curriculum will be more easily achieved. This study aims to determine the extent to which effective communication can influence the understanding of Grade X Students of SMK Pasundan 1 Bandung towards the Merdeka Curriculum. This study uses a quantitative approach with a survey method to measure the influence of the independent variable, namely effective communication (Variable X), on the dependent variable, namely students' understanding of the Merdeka Curriculum (Variable Y). This study aims to determine the influence of the dimensions of Effective Communication on the Understanding of the Merdeka Curriculum in SMK Pasundan 1 Bandung students. The results of the analysis show that partially, the Respect and Humble dimensions have a positive effect, respectively by 11.57% and 2.96%, while Empathy, Audible, and Clarity show a negative effect of -9.57%, -2.78%, and -1.92%. These findings indicate that the teacher's attitude of mutual respect and humility is more encouraging for student understanding, compared to the aspects of empathy, audibility, and clarity of messages that have not been optimized in the learning process. With data analysis and a path analysis approach, this study is expected to be able to provide an overview of the relationship between effective communication and improving the quality of learning in the school.